A Clinical and Genetic Evaluation of Cases with Folate Receptor ? Gene Mutation: A Case Series from Türkiye - Akgun, Abdurrahman; Tas, Ibrahim (Mdpi, 2025)
Background/Objectives: Cerebral folate transporter deficiency is characterized by pauses and regression in general development stages, with ataxia, choreoathetoid movements, and myoclonic epilepsy generally resistant to treatment. The aim of this study was to comprehensively evaluate cases followed up in two centres in T & uuml;rkiye for a diagnosis of folate receptor-alpha deficiency. Methods: The study included nine cases from six different families. Results: The patients comprised 22.2% males and there was parental consanguinity in 88.9% of cases. The mean age at which complaints were first noticed was 3.7 years, and the age of definitive diagnosis was 10.4 years. The most frequently seen first complaints were febrile convulsions and attention deficit-hyperactivity-learning difficulties. The diagnosis most commonly made before the definitive diagnosis was epilepsy, and the first seizure occurred at a mean of 5.2 years. On cranial imaging, white matter involvement, cerebellar atrophy and cerebral atrophy were determined most often. Definitive diagnosis was established solely through clinical findings and genetic analysis. Three different variants in the FOLR1 gene were determined. Treatment with folinic acid at a dose of 5.2 mg/kg/day of PO was started at the age of 9.8 years on average, and intravenous folinate was started at different doses. Conclusions: This study stands out as one of the largest case series in the literature and identifies a previously unreported novel variant. Our study suggests that FOLR1-related CFD should be considered in cases with febrile convulsions, developmental delay, ataxia, autism spectrum disorder, acquired microcephaly, and MRI findings of white matter involvement and cerebellar atrophy. Due to an asymptomatic early period, CFD diagnosis may be delayed, and treatment after symptom onset may be less effective. Incorporating FOLR1 gene analysis into newborn screening programmes could facilitate early diagnosis and treatment. It is thought that the application of vagus nerve stimulation, in addition to folinic acid and anticonvulsant drug treatment, could be effective in seizure control.
Keywords: cerebral folate transporter deficiency; FOLR1; 5-methyltetrahydrofolate; folic acid; folinic acid